Cooling of ejaculated and epididymal stallion sperm - G.A. Monteiro; P.N. Guasti; F.P. Hartwig; J.A. Dellaqua Jr.; M.A. Alvarenga; F.O. Papa (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2013)
After a serious injury or sudden death, epididymis cauda sperm recovery and cryopreservation may present as the last opportunity to obtain genetic material from a valuable stallion. This study evaluated the viability of cooled equine sperm collected by three different methods: sperm of ejaculated (G1), sperm recovered from the epididymal cauda immediately after orchiectomy (G2) and sperm recovered from the epididymal cauda after storage for 24 hours at 5°C (G3). To obtain G1 sperm, two ejaculates were collected. After 1 week, all stallions underwent a bilateral orchiectomy, and one of the removed epididymides was flushed to obtain G2 sperm. The contralateral epididymis was stored at 5°C for 24 hours before being flushed to obtain G3 sperm. The sperm samples were evaluated immediately after the addition of the refrigeration extender, and after 24 and 48 hours of storage at 5°C. After 24 and 48 hours of storage, the epididymal sperm demonstrated higher motility traits when compared to the ejaculated sperm (P<0.05). These results indicate that sperm recovered from the epididymal cauda of stallions are more resistant to the cooling process, with higher kinetic parameters and plasma membrane integrity when compared to the ejaculated sperm.